Theatre & performance, crisis & survival. Issue 3 (3rd July 2019) - Solga, Kim
ABSTRACT: In this introduction, guest editor Kim Solga reflects on the origins of the issue, details its scope, offers grounding definitions of 'neoliberalism' and 'the neoliberal university', and charts one possible way forward, in hope.